1988
DOI: 10.1523/jneurosci.08-01-00064.1988
|View full text |Cite
|
Sign up to set email alerts
|

Developmental decrease in size of peripheral receptive fields of single chorda tympani nerve fibers and relation to increasing NaCl taste sensitivity

Abstract: During development in rats, sheep, and humans, the taste system acquires increasing responsiveness to NaCl, compared with a variety of other salts and chemicals. To better understand the neural basis of changes in salt taste responses, we studied receptive field size and response properties of single chorda tympani nerve fibers in fetal, perinatal, and postnatal sheep. Individual fungiform papillae were stimulated electrically with 5 microA anodal current to determine the location and number of papillae in rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 21 publications
3
68
2
Order By: Relevance
“…In cats, single geniculate ganglion cells responded to electrical stimulation of single buds in only one-fifth of tested neurons; fourfifths responded to two to five nearby buds (Boudreau et al, 1971). More recently, a similar result was obtained in sheep using more refined methods (Nagai et al, 1988). Thus, species differences in the selectivity of bud innervation by single ganglion cells seem likely.…”
Section: Bud Units In Mousesupporting
confidence: 63%
“…In cats, single geniculate ganglion cells responded to electrical stimulation of single buds in only one-fifth of tested neurons; fourfifths responded to two to five nearby buds (Boudreau et al, 1971). More recently, a similar result was obtained in sheep using more refined methods (Nagai et al, 1988). Thus, species differences in the selectivity of bud innervation by single ganglion cells seem likely.…”
Section: Bud Units In Mousesupporting
confidence: 63%
“…In developing sheep, there is a selective pruning of receptive fields for neurons that become responsive to sodium stimuli, while the receptive fields of other neuron types remain relatively large. 47 These data are important not only from a developmental framework (because they reveal structure/function relationships between taste receptors and afferent neurons during gustatory development), but also because they strongly suggest that such relationships may be modifiable through environmental factors. Such studies await examination.…”
Section: Plasticity Of Neuron/target Matchingmentioning
confidence: 99%
“…The simplest description of the relationship between an afferent fiber of a GG/CT and the fungiform papillae that it innervates is that the axon travels to the tongue and then divides to innervate from one to eight fungiform papillae, forming a complex taste end organ. However, a number of investigators have demonstrated that characteristics of fungiform receptive field innervation are highly complex Nagai et al 1988). …”
Section: Receptive Field Characteristics Of Gg/ct Neuronsmentioning
confidence: 99%
“…In fact, it has been known for some time that, like finger mechanoreceptors, single CT afferent fibers terminate in fungiform taste buds that are organized in receptive fields. Investigators using rat (Miller 1971), cat (Boudreau et al 1971;Oakley 1975;Robinson 1988), goat (Boudreau et al 1985) and sheep (Nagai et al 1988) have shown that CT fiber receptive fields vary in size, ranging from 1 to 13 papillae. However, prior investigators have concentrated on the responses of GG neurons to chemical stimulation of the anterior tongue and omitted comprehensive study of the basic neurobiological properties of the GG neurons that include receptive field size, associated CT fiber properties and responses to nongustatory stimuli.…”
mentioning
confidence: 99%
See 1 more Smart Citation